“White spots” in the diagnostic search for the causes of recurrent miscarriage - E. Yu. Lebedenko; Ar. A. Mikhelson; A. A. Mikhelson; V. A. Zmienko; A. S. Sagamonov; H. Yu. Kormanukov (Медицинский вестник Юга России, 2024)
Recurrent pregnancy loss is not only a medical, but also a social problem of a multifactorial nature. This problem remains unsolvable despite the constant search and application of new diagnostic and therapeutic strategies. The presented review examines the literature data on evidence-based methods for diagnosing the causes of miscarriage, as well as methods whose use remains controversial. Special attention is paid to the immunological foundations of a normal pregnancy formation, the violation of which creates the prerequisites for a recurrent miscarriage. The paper also analyzes current data on the role of endometrial receptivity and the contribution of the male factor to the problem of miscarriage, and presents prospects for further research on the problem of recurrent pregnancy loss.